Diagnostic uncertainty between cystic fibrosis and allergic bronchopulmonary aspergillosis in a young adult male: a case report - Giripunje, Pranay; Singh, Harsimar; Roy, Sunita; Paul, Uttam Kumar (International Journal of Advances in Medicine, 2025)
A 23-year-old male presented with persistent respiratory issues and HRCT findings indicating bronchiectasis. Both cystic fibrosis (CF) and allergic bronchopulmonary aspergillosis (ABPA) were considered due to overlapping clinical and radiological features. Notably, elevated Aspergillus-specific IgE levels supported ABPA, while systemic and reproductive features pointed towards CF. This case exemplifies the diagnostic complexity when two conditions with converging presentations must be carefully distinguished.